Coagulation Team-Based Learning Exercise - Marc Kahn; Craig Clarkson; Byron Crawford (Association of American Medical Colleges, 2009)
Abstract This resource is a team-based learning module on coagulation. It is used in Tulane University School of Medicine's second-year mechanisms of disease course. This module was specifically developed for the hematopathology section of the course, which comprises 20 hours of material including lecture, case-based learning exercises, online cases, and this resource. This team-based learning was well-received by our students, receiving a Likert score of 3.93 out of 4.00 for overall content. It is an effective method to teach basic principles of coagulation with venous thromboembolism as a clinical correlate.